(untitled) - Du Ngoc Bich (Neitherland, 2006)
The study is focus on developing a proposal for new Vietnamese legislation on recognition and enforcement of foreign judgement when no treaty applies.
Keywords: Conflict of laws,Private international law; Cases; Vietnam